2009
DOI: 10.1074/jbc.m109.005272
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-driven Th2 Cytokine Production in Macrophages Is Regulated by Both MyD88 and TRAM

Abstract: Gram-negative bacterial lipopolysaccharide (LPS) activates macrophages by interacting with Toll-like receptor 4 (TLR4)and triggers the production of various pro-inflammatory Th1 type (type 1) cytokines such as IFN␥, TNF␣, and IL8. Though some recent studies cited macrophages as potential sources for Th2 type (type 2) cytokines, little however is known about the intracellular events that lead to LPS-induced type 2 cytokines in macrophages. To understand the mechanisms by which LPS induces type 2 cytokine gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 40 publications
0
48
0
1
Order By: Relevance
“…1 and 2). Previous studies have shown that macrophages express TNF mRNA (43) and that LPS augments their TNF expression at both the mRNA and protein levels (44,45). Secretion of TNF by adipose tissue has also been described (37,46,47), but it presumably had originated from macrophages residing within the tissue (48).…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2). Previous studies have shown that macrophages express TNF mRNA (43) and that LPS augments their TNF expression at both the mRNA and protein levels (44,45). Secretion of TNF by adipose tissue has also been described (37,46,47), but it presumably had originated from macrophages residing within the tissue (48).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] An increased serum level of IL-4 might be the result of a high endotoxin concentration because LPS drives the production of both Th1 and Th2 cytokines. 27 Zhou et al 18 have shown that feeding apoEϪ/Ϫ mice an HFD containing 1.25% cholesterol and 0.5% cholic acid induces a shift from the Th1-type to the Th2-type immune response, with increased IL-4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenesis by LPS is due to strong Th2 immune deviation (Mukherjee et al, 2009). However, CpG ODNs are able to inhibit the established Th2 immune responses against antigen, converting these to Th1 immune responses.…”
Section: Discussionmentioning
confidence: 99%